Narrating the Destination Through Food: An Empirical Study of Cultural Cuisine, Tourist Engagement, and Attractiveness - Chendraningrum, Dinarsiah; Suryana, Marceilla (Politeknik Negeri Bandung, 2025)
This study examines the role of culturally rooted cuisine in shaping tourist satisfaction and enhancing the perceived attractiveness of destinations within the broader framework of cultural tourism. Based on responses from 289 participants, the research analyzes four core constructs: the culinary encounter, depth of cultural engagement, the symbolic perception of traditional food practices, and the educational dimensions embedded in gastronomic experiences. These variables are evaluated concerning their influence on both emotional resonance (affective response) and rational appraisal (cognitive evaluation) among visitors. Findings demonstrate that culturally rooted cuisine transcends mere sensory enjoyment, serving instead as a potent vehicle for cultural immersion and informal learning. Each hypothesized relationship is statistically significant, with tourist satisfaction emerging as the most critical predictor of destination appeal. Of particular interest is the educational value derived from food-related experiences—framed as the transmission of cultural and historical knowledge through cuisine—which simultaneously reinforces tourist satisfaction and enriches perceptions of the destination. The conceptual framework synthesizes insights from experiential marketing, destination image Theory, and scholarship on cultural consumption—the research positions cuisine as a dynamic and expressive medium of cultural identity. From a managerial perspective, the findings underscore the strategic importance of curating culinary experiences that are narratively rich, participatory in nature, and deeply embedded in local cultural contexts.